Proof: Transitive Property Application 7

Let's prove the following theorem:

if the following are true:
  • a = b
  • b = c
  • c = d
  • d = e
  • e = f
  • f = g
  • g = h

then a = h

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 a = b
2 b = c
3 c = d
4 d = e
5 e = f
6 f = g
7 g = h
Proof Table
# Claim Reason
1 a = g if f = g and e = f and d = e and c = d and b = c and a = b, then a = g
2 a = h if g = h and a = g, then a = h

Comments

Please log in to add comments